Human-centered higher education reform in Vietnam - Dung Huy Nguyen; AnLong Dang Nguyen (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study uses an explanatory sequential mixed-methods design to assess the level of implementation and effectiveness of human-centered higher education innovation in Vietnam in the context of digital transformation and international integration. Instead of just analyzing policy directions, the study focuses on evaluating: i) the level of awareness of educational stakeholders regarding four content groups (technology, culture-humanities, integration, and humanities); ii) the implementation gap between direction and practice; and iii) the relative weight of each group of factors in educational innovation. Quantitative data were collected from 247 survey responses and analyzed using repeated measures ANOVA. The results showed statistically significant differences between the content groups (F(3,247)=15.32; p<0.001; η²=0.24), with the “human-centered” group having a significantly higher average score than the technology and integration group. The statistically insignificant difference between the human group and the culture group suggests a complementary relationship between these two factors. The research results provide empirical evidence that human-centered indicators can be used as evaluative benchmarks for educational innovation in the context of developing countries.